Phylogenetic and Genetic Diversity of Local Durian (Durio spp.) from Siberut Island within Southeast Asia: Insights from rbcL and ITS Markers: Phylogenetic and Genetic Diversity of Local Durian from Siberut Island - Alponsin; Mansyurdin; Nurainas (Journal of Tropical Life Science, 2026)
This study examined the genetic diversity and phylogenetic relationships of Durio species from Siberut Island, Indonesia, within the broader Southeast Asian context, utilizing two molecular markers: rbcL and ITS. Leaf samples underwent DNA sequencing, followed by genetic distance estimation, phylogenetic reconstruction, and haplotype network analysis. The ITS marker exhibited high discriminatory power, effectively differentiating species and revealing distinct haplotype variation among populations, while resolving distinct clades with strong bootstrap support. Conversely, the rbcL marker, being highly conserved, provided reliable resolution at the genus level but was inadequate for distinguishing closely related species. A significant finding is the close genetic affinity between the wild variety Toktuk Geta from Siberut and D. singaporensis, a species previously recorded in Peninsular Malaysia. This association may indicate an unrecognized lineage or historically disjunct distribution, although confirmation necessitates broader sampling and additional markers. Substantial genetic differentiation was observed among D. zibethinus populations across Southeast Asia (FST = 0.49293), aligning with restricted gene flow among geographically distinct populations. These findings suggest that ITS is a suitable marker for species-level phylogenetics in Durio, whereas rbcL is more appropriate for genus-level identification. The unique genetic composition of Durio germplasm on Siberut Island highlights the conservation value of this region for plant genetic resources in the Mentawai Archipelago.